Getting ready for PROPER and other policies: global learnings and key success factors for Indonesia - Eric Mieras; Jessica Hanafi; Marisa Vieira; Anne Gaasbeek; Laura Golsteijn (Indonesian Life Cycle Assessment Network (ILCAN), 2018)
Indonesia introduced new policies, like PROPER, that require companies to develop LCA capacity. Currently, LCA expertise is still developing. Therefore, the question arises how the development of LCA expertise and a growth of LCA Practitioners can be achieved. In this article learnings and key success factors from global best practices are identified and illustrated based on case studies. The key success factors are 1) harmonization and guidance, 2) capacity building, 3) focus on business value and 4) ease of use. These Key Success Factors can give Indonesia and its LCA practitioners a head start in implementing and embedding LCA in policy implementation and compliance by private companies. Developing a program that provides the following six elements a) Introduction to LCA training, b) Training for managers and policy makers, c) Learning by doing with screening LCAs, d) Facilitate easy to use tools, e) Develop Product Category Rules (PCR) and f) Create a label or other verified report/certificate can accelerate the development of LCA expertise and the implementation of LCA practices.